Combinations of radiotherapy with vaccination and immune checkpoint inhibition differently affect primary and abscopal tumor growth and the tumor microenvironment - Rückert, Michael; Deloch, Lisa; Frey, Benjamin; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo (Cancers, 2021)
Radiotherapy (RT) is known to have immune‐modulatory properties. We hypothesized that RT and inactivated whole tumor cell vaccines generated with high hydrostatic pressure (HHP) synergize to retard the tumor growth which can be additionally improved with anti‐PD‐1 treatment. In abscopal tumor models, we injected mice with B16‐F10 melanoma or TS/A mammary tumors. To evaluate the efficiency of RT in combination with HHP vaccines, we locally irradiated only one tumor with 2 × 8 Gy or 3 × 8 Gy. HHP vaccines further retarded the growth of locally irradiated (2 × 8 Gy) tumors. However, HHP vaccination combined with RT failed to induce abscopal anti‐tumor immune responses, namely those to non‐irradiated tumors, and even partly abrogated those which were induced with RT plus anti‐PD‐1. In the latter group, the abscopal effects were accompanied by an elevated infiltration of CD8+ T cells, monocytes/macrophages, and dendritic cells. 3 × 8 Gy failed to induce abscopal effects in association with increased expression of immunosuppressive checkpoint molecules compared to 2 × 8 Gy. We conclude that HHP vaccines induce anti‐tumor effects, but only if the tumor microenvironment was previously modulated by hypofractionated RT with not too many fractions, but failed to improve RT plus anti‐PD‐induced abscopal responses that are characterized by distinct immune alterations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Abscopal effect; High hydrostatic pressure; Immune checkpoint inhibition; Radiotherapy; Tumor microenvironment; Tumor‐infiltrating immune cells; Vaccination